Naturalis, Dokter, dan Ahli Ilmu Bumi - Jaelani, Gani Achmad (Jurnal Sejarah, 2019)
This article aims to elaborate earthquakes and the eruption researches in the nineteenth century Indonesia. The practice that involves naturalists, physicians, and earth scientist has a purpose to discover more about the natural world of the Tropics. Each of these agents has different issues in questioning this matter, but the objectives are the same: to understand the danger provoked by this natural phenomenon. Their works could be read in scientific journals in the nineteenth century. In the colonial state, their research could be read as well as the way the colonial government to assure their interest far from the danger such as the earthquake and the volcanic eruption. This article will try to analyse how these three agents observed the earthquakes and volcanic eruption in the nineteenth century; to what extent this practice correspond to the colonial politics. Lastly, this article will analyse the relation between the natural science and colonialism in the Netherlands Indies. Keywords: Earthquakes, colonialism, scientific research, natural science, Netherlands-Indies, volcanic eruption